ТРАКТУВАННЯ ПОНЯТТЯ “ЕСТЕТИЧНА КУЛЬТУРА” У ПСИХОЛОГО-ПЕДАГОГІЧНІЙ ЛІТЕРАТУРІ (Педагогіка вищої та середньої школи, 2022)
The article “Treatment of concept “aesthetic culture ” in the psychical-pedagogical literature ” is devoted to the analysis of various treatments of concept “aesthetic culture ” that has allowed the author to make the generalization necessary for it for carrying out of the further research work.